If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + 9 = 13 + -2(y + 3) Reorder the terms: 9 + 4y = 13 + -2(y + 3) Reorder the terms: 9 + 4y = 13 + -2(3 + y) 9 + 4y = 13 + (3 * -2 + y * -2) 9 + 4y = 13 + (-6 + -2y) Combine like terms: 13 + -6 = 7 9 + 4y = 7 + -2y Solving 9 + 4y = 7 + -2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2y' to each side of the equation. 9 + 4y + 2y = 7 + -2y + 2y Combine like terms: 4y + 2y = 6y 9 + 6y = 7 + -2y + 2y Combine like terms: -2y + 2y = 0 9 + 6y = 7 + 0 9 + 6y = 7 Add '-9' to each side of the equation. 9 + -9 + 6y = 7 + -9 Combine like terms: 9 + -9 = 0 0 + 6y = 7 + -9 6y = 7 + -9 Combine like terms: 7 + -9 = -2 6y = -2 Divide each side by '6'. y = -0.3333333333 Simplifying y = -0.3333333333
| 5(5)-4(5-3)=17 | | 2/3*n=24 | | n^(9/2)*n^(-5/2) | | 18+5w=8w | | 5(5)-4(-5-3)=17 | | 6x-18=7x+13 | | 15/2×1/3 | | 150x-3x^2=1000 | | x^2-21x+100=80 | | (4a^4)(b^4)(b^4)=(4ab)4 | | 24x+32x=32 | | 15/2×1/3×1/5 | | 11(11.21)-10= | | -9-b+b=-23 | | -8-12x=7-2x-6 | | 18a^3b^5+23b^2+5=0 | | 3(x-3/4)= | | .5x(5-7x)=8-(4x+6) | | 6p-5=7p+7-p | | h=-16t^2+100t+600 | | 15x^2-66x-45=0 | | 144+x^2=225 | | 84x^2-20xy+12x=0 | | 9/10y-3/5y | | 5x-20+11x-10+x+40=180 | | 12/(19x-4)=3/(5x) | | 81/y*3=27 | | a-15=22 | | 7(d-5)+9= | | 3a-12=36 | | -6x+4=-12 | | log(x)+log(x-1)=log(20) |